GPS and computer maps - Quinlan, Julia J. (New York : PowerKids Press, 2012)
"Explains the concept of Global Positioning System, or GPS--how it works, why it was developed, and how it is used to create online maps"--Provided by publisher.
Includes index.
3.9
3-6
3-6
Keywords: Digital mapping -- Juvenile literature; Global Positioning System -- Juvenile literature; Digital mapping; Global Positioning System; Digital mapping; Global Positioning System